Physical activity to overcome the adversity of widowhood: Benefits beyond physical health. Issue 32 (August 2016) - Li, Chu-Shiu; Lee, June Han; Chang, Ly-yun; Liu, Chwen-Chi; Chan, Yan-Lan; Wen, Christopher; Chiu, Mu-Lin; Tsai, Min Kuang; Tsai, Shan Pou; Wai, Jackson Pui Man; Tsao, Chwen Keng; Wu, Xifeng; et al.
Abstract : Abstract: Widowhood has been increasingly encountered because of increasing longevity of women, often characterized by social stigmatization and poor physical and mental health. However, applied research to overcome its adversity has been quite limited. The goal of this study is to explore the role of physical activity in improving the health of widows. A cohort of 446, 582 adults in Taiwan who successively participated in a comprehensive medical screening program starting in 1994, including 232, 788 women, was followed up for mortality until 2008. Each individual provided detailed health history, and extensive lab tests results. The number of widows increased with time trend. Every other woman above age 65 was a widow (44%). Widows were less active, more obese, and smoked and drank more, had sleep problems, were more depressed with taking sedatives or psychoactive drugs, leading to more suicides. In the global development of health policies by World Health Organization (WHO), physical activity is one of the main factors to reverse poor health. The poor health of inactive widow was mitigated when becoming fully active in this study. Exercise not only reduced the observed 18% increase in all-cause mortality, but also gained 4 years and as much as 14% mortality advantage over the married but inactive. More importantly, becoming physically active energized their mental status, improved sleep quality and quantity, reduced depressions and the need for psychoactive drugs, and increased socialization circles. Widows, a rapidly growing and socially stigmatized group, suffered from social and financial inequality and tended to develop poorer health. Sustained physical activity could be one of the ways for them to overcome and reverse some of the physical and mental adversities of widowhood, and improve their quality and quantity of life. Abstract : Supplemental Digital Content is available in the text